Combining Ability Estimates in Heat Tolerant Tomato (Solanum lycopersicum L.) Genotypes - Ahmad, S; Quamruzzaman, AKM; Uddin, M Nazim (The Agriculturists, 2010)
The experiment was conducted at the experimental farm of Olericulture Division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur from May to August 2003. Combining ability effects were estimated for yield and component traits in a 8 x 8 diallel design excluding reciprocals in tomato. The variances for general combining ability (GCA) and specific combining ability (SCA) were highly significant indicating the presence of additive as well as non-additive gene effects in the traits studied. The relative magnitude of these variances indicated that additive gene effects were more prominent for all the characters under study. The tomato genotype P1 (TM051) proved to be the best general combiner for yield followed by P2 (TM053) and the combinations P1xP3, P1xP5 and P5xP7 were identified as the best specific combiner for earliness, yield per plant, number of fruits per plant and individual fruit weight.